4.1: The influence of adhesives and binders resistivities on the optic performance of electrophoretic display modules. (28th November 2018) - Ma, Baoguang; Guo, Yulin; Luo, Yujie; Zeng, Xi; Chen, Yu
Abstract : With broad commercial applications of electrophoretic display, it is important to continuously improve its optic performance, including white reflectivity, dark reflectivity, response time, holding time, etc. However, due to the complexity of electrophoretic modules, the display performance is influenced by numerous factors. Among these factors, the resistivities of electrophoretic modules adhesives and binders are essential due to their significant influence on the voltage applied to the electrophoretic layer. In this paper, the adhesives and binders with different resistivities, which are commercially used, are investigated. The results show that the decrease of resistivities in adhesives and binders are beneficial for display performance.